MORPHOLOGY OF THE SALIVARY-GLAND ACINI IN GRIGIOTERMES-BEQUAERTI (ISOPTERA, TERMITIDAE, APICOTERMITINAE) - Costaleonardo, A. M.; Dacruzlandim, C. (E Schweizerbart'sche Verlags, 1991)
The salivary glands of females in Grigiotermes bequaerti (Snyder & Emerson 1949) are composed of many acini. Within the acini, the secretion is collected by canals that join into excretory ducts that open at the acini are formed of 3 classes of cells: secretory, parietal and canalicular. The secretory cells present 2 distinct types which, however, seem to be only different functional stages. Their secretion appears to be highly fluid and accumulates in vacuoles of low electron density. The morphological features of parietal cells point to an ionic transportation function, since they contain an intracellular canaliculus lined with microvilli, and are rich in mitochondria. The final product of the gland may result from the interaction of these 2 cells. The canicular cells located within the acini, in addition to constituting the way of secretion elimination, may have a support function serving as a point of aggregation an interconnection of secretory and parietal cells.
Keywords: EXOCRINE GLANDS; SALIVARY GLANDS; GLANDULAR ULTRASTRUCTURE; ISOPTERA; TERMITIDAE